Fratura proximal de fêmur : estudo de uma coorte residente em Assis-SP - Pacheco, Cássia Regina Saade (2007)
The Proximal Femoral Fracture (PFF) is said to be the most serious and devastating consequence of the osteoporosis due to hospitalization and surgical treatment demand and to be able to produce functional incapacity and mortality, mainly at a great age in association with co-morbidity. Affecting mainly women, the PFF requires care provided by the family as a caretaker, even so the rehabilitation process must begin in the hospital stage, assuring the patient to have an early mobilization and independence. This research was based on a retrospective and observation cohort study aiming to know the physical and psycho-socialeconomical aspects of PFF to relate the fracture causes to the osteoporosis and the discernment of the osteoporosis. This research studied 81 subjects (age 77,43 +/- 10,78), men and women (73%) living in Assis at the age of >/= 40, internal patient at Charity Association Santa Casa de Assis for treatment of PFF for trauma of low energy. There were at SAME 103 selected handbooks dated from January, 2002 to December, 2004 being excluded 22 subjects during the study. The data were obtained through a questionnaire (133 subjects) in home visit. This cohort showed 100% of surgical treatment (98% by SUS, 2% by IAMSPE) for fracture of femoral neck (58%), with osteossintesis (61%); higher incidence at a great age (77,43 +/- 10,78), woman (78%), sedentary (98%) who took care of the home (49%); due to fall of the own height (87%) at home (77%), being demanded caretaker s presence (98%) family (87%). The pointed co-morbidity (79%) was the hypertension (20%) and cardiopathy (18%). The mortality population (36%) and the non-recovery (17%) showed a significant increased age (p < 0,05) compared to those recovered (47%). 55% of the deaths happened 3 months after PFF recovery. The Physiotherapy was shown important to the recovery in this cohort with low osteoporosis discenment. Education directions to the population and physical activity practices at a great age are necessary to prevent from falls and death or disability as a PFF consequence.